2021
DOI: 10.1016/j.foodcont.2021.108084
|View full text |Cite
|
Sign up to set email alerts
|

Surveying the impact of the coronavirus (COVID-19) on the poultry supply chain: A mixed methods study

Abstract: The coronavirus pandemic (COVID-19) has affected all supply chains through severe disruption of logistics activities, production, and markets. This study aimed to survey the impact of the coronavirus on the poultry supply chain using an exploratory sequential mixed design. We first addressed those stages of the poultry supply chain disrupted in an ongoing pandemic, and then elaborated particular disturbances associated with each stage. This study was based on data collected from Iranian poultry industry owners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…Indeed, "the pandemic has made consumers more concerned about their own food safety" (Palouj, et al, 2021). Moreover, the disruption of the global supply chain both forced and encouraged consumers to buy domestic/locally produced products (Ben Hassen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, "the pandemic has made consumers more concerned about their own food safety" (Palouj, et al, 2021). Moreover, the disruption of the global supply chain both forced and encouraged consumers to buy domestic/locally produced products (Ben Hassen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The country's economic engine has picked up some speed in June, as the number of manufacturing units has opened with a very small labor force during lockdown 3.0. The actual situation of agricultural commodity prices will be known once the lockdown is over [15].…”
Section: Economic Impact Of Covid-19 Spread In Indian Agriculture And...mentioning
confidence: 99%
“…In the primary sector, Palou et al [ 37 ] used the fuzzy delphi method (FDM) and the fuzzy analytical hierarchy process (FAHP) to study the impact of the COVID-19 pandemic on the Iranian poultry supply chain. The authors identified disruptions associated with each stage of the production chain, suggesting that the pandemic has further affected input supply as a stage in the poultry supply chain.…”
Section: Applications Of Different Fuzzy Techniques On First Covid-19 Wave In Hospital Emergenciesmentioning
confidence: 99%